Genetic characterization of Streptococcus equi subspecies zooepidemicus associated with high swine mortality in the United States. Issue 6 (13th June 2020) - Chen, Xuhua; Resende‐De‐Macedo, Nubia; Sitthicharoenchai, Panchan; Sahin, Orhan; Burrough, Eric; Clavijo, Maria; Derscheid, Rachel; Schwartz, Kent; Lantz, Kristina; Robbe‐Austerman, Suelee; Main, Rodger; Li, Ganwu
Abstract: High mortality events due to Streptococcus equi subspecies zooepidemicus ( Streptococcus zooepidemicus ) in swine have not previously been reported in the United States. In September and October 2019, outbreaks with swine mortality up to 50% due to S. zooepidemicus septicaemia were reported in Ohio and Tennessee. Genomic epidemiological analysis revealed that the eight outbreak isolates were clustered together with ATCC 35246, a Chinese strain caused outbreaks with high mortality, also closely related to three isolates from human cases from Virginia, but significantly different from an outbreak‐unrelated swine isolate from Arizona and most isolates from other animal species. Comparative genomic analysis on two outbreak isolates and another outbreak‐unrelated isolate identified several genomic islands and virulence genes specifically in the outbreak isolates only, which are likely associated with the high mortality observed in the swine population. These findings have implications for understanding, tracking and possibly preventing diseases caused by S. zooepidemicus in swine.